MARKETING RESEARCH MANAGEMENT IN THE DIGITAL ECONOMY - Kasimova Fatima Tulkunovna; Khakimova Nasiba Kakhramonovna; Xaydarova Kamola Axinjanovna; Aliyeva Janat Askarovna; Baymukhamedova Gulnaz Fattakhovna (Utilitas Mathematica, 2025)
In the era of rapid digital transformation, marketing research management has undergone significant changes. The digital economy, characterized by the widespread use of digital technologies, big data, and online platforms, has redefined how organizations gather, analyze, and utilize market information. This paper explores the evolving role of marketing research in the digital economy, highlighting the integration of advanced tools such as artificial intelligence, machine learning, and data analytics in decision-making processes. The study examines challenges such as data privacy, information overload, and the need for skilled analysts, while also identifying emerging opportunities for real-time insights, consumer behavior tracking, and personalized marketing. Effective marketing research management in this context requires adaptive strategies, technological proficiency, and a customer-centric approach. The findings underscore the importance of aligning traditional research principles with innovative digital practices to remain competitive in the modern marketplace.